Hip–Knee Coupling Exoskeleton With Offset Theory for Walking Assistance - Ma, Jianfeng; Sun, Decheng; Chen, Xiao (Frontiers in Bioengineering and Biotechnology, 2022)
To alleviate the influence of aging on the elderly, this paper designs a hip-knee coupling exoskeleton with offset theory to improve people's athletic ability. With the novel design, the unique application strategy of the offset principle for hip and knee joint is developed and a hip-knee coupling mechanism is proposed to solve the discrete power-assistance problem for the knee joint. To acquire the success of the design, the mathematical model of the coupling mechanism is established to optimize the load environment of the exoskeleton system, and further an algorithm adapted to human movement is proposed to determine the monotonicity of the cam profiles. For the selection of the elastic parameters in the coupling mechanism, the sensitivity condition is proposed and the human-machine interaction model of the KESM is further established. A man-machine coupling model was used to verify the scientificity of the exoskeleton design, and the comparison between the joint powers with or without exoskeleton indicated that the exoskeleton theoretically saved at least 20% of the human body's energy.